Análise das ações e serviços públicos de saúde do município de Sabará∕MG de acordo com as normativas do SUS - Marília Kathya Coutinho (2021)
The general objective of this study was to analyze the actions and public health services of the municipality of Sabará/MG, according to the SUS Parameter and Normative Notebook related to planning. The specific objectives were: to identify the epidemiological indicators of the municipality of Sabará/MG, necessary for the calculation of estimates of health actions, presented in the SUS 2020 Parameter Notebook; to estimate the health actions and services, defined by SUS 2020 Parameter and Normative Notebook for the municipality of Sabará/MG and the health actions carried out in the territory of Sabará/MG; comparatively analyze the actions produced by the municipality of Sabará/ MG with those estimated by the SUS Parameter Notebook 2020. The theoretical framework addressed the following themes: the sus regulations, the planning in the SUS and its instruments; the analysis of the health situation of Sabara/MG and the SUS Parameter Notebook 2020. The rules related to planning, regionalization and the Health Care Network of Sabará/MG (RAS) were also addressed. As for the method, this is a documentary study and descriptive purposes. The data needed for the diagnosis of the health situation of the municipality of Sabará/MG were collected in the DATASUS databases, mainly demographic data, referring to the distribution of the total population of the municipality separated by gender and age group, the data of general mortality and causes and hospitalization data by range, and by group of causes. Data regarding physical, human and material resources and equipment were obtained in the CNES. Other socioeconomic data, such as per capita income, employment status, schooling, and general sanitation conditions, were identified from the database of the Municipality of Sabará/MG and in the PNAD continua of IBGE. The Municipal Health Plan of Sabará/MG and the Management Report 2020 were also analyzed. Descriptive mathematics was used for data analysis. The analysis of these data allowed the identification of several vulnerable populations, including children under 1 year of age, adolescents, women of childbearing age and finally the elderly. The analysis of socioeconomic indicators showed the fragility of one third of the population living on half a minimum wage, in addition to identifying that those belonging to the black, brown and indigenous race are the ones who suffer the most from the consequences of social inequalities. The analyses of the indicators of the Stork Network show a significant decrease in maternal and infant mortality in the last 20 years. However, the analysis of these data suggests important deficiencies in the policies of women's and adolescents' health care, which, in addition to pregnancy, suffer from violent causes. Regarding the health of children under 1 year, especially in the first seven days of life, they have a perinatal mortality rate well above the General Mortality Rate. Based on infrastructure estimates for the Stork Network, the municipality needs 22 obstetric beds for pregnant women at normal risk, and 2 for high-risk pregnant women, three adult ICU beds and three neonatal ICU beds, since they do not have obstetric and ICU beds in their territory. The number of specialized consultations needed to ensure the assistance of the population was one third of the need. Failures in vaccination coverage of both children and adults were also identified. In the population over 60 years of age, the main cause of hospitalization was diseases of the circulatory system. The main consequences of cardiovascular diseases, diabetes and chronic kidney disease are demonstrated in hospital morbidity, and in the demand for diagnostic and therapeutic tests. The need for dialysis also proves the undesirable evolution of chronic pathologies. The number of procedures performed by the ESF and the ESB are much lower than those estimated by the SUS Parameter Notebook. The number of ESF is estimated at 68 teams, and the 22 existing teams are insufficient to meet the needs identified in the municipality. The number of professionals for primary care is undersized, as there is a lack of Family Physicians, Pediatricians, Gynecologists, Surgeons, Nurses, Nursing Technicians, Community Health Agents. For 8 Oral Health Teams there are only 5 dentists in the family. Also missing several specialists According to the SUS Parameters 2020, Sabará needs at least 351 beds while the number of beds contracted are 108. The analysis of the estimated and existing diagnostic support equipment in the territory demonstrates that they are absent or undermentioned. With this work, it became evident the fragmentation of the data presented in the sources consulted, leaving implicit the lack of coordination at the time of their insertion in the various platforms used by the Ministry of Health. The study revealed the importance of the SUS 2020 Criteria and Parameters as a normative reference and guide of public health actions and services in Brazilian municipalities, and in Sabará/MG, in particular. It is perceived the need for greater transparency of municipal management reports, with the correct feeding of the data produced, in the Platforms of the MS, in order to enable the effective social control of the actions carried out in the municipality.